2009
DOI: 10.1111/j.1471-4159.2009.06253.x
|View full text |Cite
|
Sign up to set email alerts
|

Fractalkine‐induced activation of the phosphatidylinositol‐3 kinase pathway attentuates microglial activation in vivo and in vitro

Abstract: Several neurodegenerative disorders are associated with evidence of inflammation, one feature of which is increased activation of microglia, the most likely cellular source of inflammatory cytokines like interleukin‐1β. It is now recognized that interaction of microglia with other cells contributes to maintenance of microglia in a quiescent state and the complementary distribution of the chemokine, fractalkine (CX3CL1) on neurons and its receptor (CX3CR1) on microglia, suggests that this interaction may play a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
167
1

Year Published

2009
2009
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 179 publications
(178 citation statements)
references
References 46 publications
(107 reference statements)
10
167
1
Order By: Relevance
“…Whereas CD200 is widely distributed, CD200 receptor expression is confined to cells of the myeloid lineage; consequently co-culturing of neurons with microglia decreases lipopolysaccharide (LPS)-or amyloid-β (Aβ)-induced microglial activation and this is dependent on interaction of CD200 with its receptor (Lyons et al, 2007a;Lyons et al, 2009b). The largely complementary expression of fractalkine on neurons and its receptor on microglia (Harrison et al, 1998) suggests an interaction similar to that described for CD200-CD200R, and evidence to support this has been reported (Cardona et al, 2006;Lyons et al, 2009a). CD45 and signal regulatory protein (SIRP)1α, which are expressed predominantly on microglia, interact with neuronally expressed CD22 and CD47 respectively (Biber et al, 2007;Mott et al, 2004).…”
Section: What Factors Contribute To the Maintenance Of Microglia In Amentioning
confidence: 53%
See 1 more Smart Citation
“…Whereas CD200 is widely distributed, CD200 receptor expression is confined to cells of the myeloid lineage; consequently co-culturing of neurons with microglia decreases lipopolysaccharide (LPS)-or amyloid-β (Aβ)-induced microglial activation and this is dependent on interaction of CD200 with its receptor (Lyons et al, 2007a;Lyons et al, 2009b). The largely complementary expression of fractalkine on neurons and its receptor on microglia (Harrison et al, 1998) suggests an interaction similar to that described for CD200-CD200R, and evidence to support this has been reported (Cardona et al, 2006;Lyons et al, 2009a). CD45 and signal regulatory protein (SIRP)1α, which are expressed predominantly on microglia, interact with neuronally expressed CD22 and CD47 respectively (Biber et al, 2007;Mott et al, 2004).…”
Section: What Factors Contribute To the Maintenance Of Microglia In Amentioning
confidence: 53%
“…These interactions appear to function as 'off' signals as do secreted CD22 and fractalkine (Biber et al, 2007), neurotrophins and anti-inflammatory cytokines such as interleukin (IL)-10 and IL-4 (Biber et al, 2007;Lyons et al, 2007b). These factors attenuate changes induced in microglia by stimuli that include interferon- (IFN), LPS and Aβ (Clarke et al, 2008;Lyons et al, 2007b) and, interestingly, age-related decreases in expression of several of these 'off ' signals have been reported (Lyons et al, 2009a;Moore et al, 2007;Nolan et al, 2005). …”
Section: What Factors Contribute To the Maintenance Of Microglia In Amentioning
confidence: 99%
“…CX3CL1 is constitutively expressed in the nervous system, but levels in the brain can be modulated under diverse pathological conditions (Pan et al, 1997;Hughes et al, 2002;Kastenbauer et al, 2003;Sunnemark et al, 2005;Huang et al, 2006). The presence and the stimulation (Zujovic et al, 2000(Zujovic et al, , 2001Mizuno et al, 2003;Cardona et al, 2006;Lyons et al, 2009) of the CX3CL1 receptor CX3CR1 has been correlated with a reduced release of interleukin-1-b (IL-1-b) and tumor necrosis factor-a (TNF-a) from microglial cells and a lower rate of neuronal degeneration in different experimental models of neuropathologies such as experimental autoimmune encephalomyelitis, 1-methyl-4-phenyl-1,2,3,6 tetrahydropyridine hydrochloride striatal injection, lipopolysaccharide administration, and superoxide dismutase (SOD1) mutation (Huang et al, 2006;Cardona et al, 2006). These data attest to a role of the pair CX3CL1/CX3CR1 in reducing neuronal degeneration on several types of brain injury.…”
Section: Introductionmentioning
confidence: 99%
“…The majority of studies have shown that the expression of FKN is elevated in neurons under physiological conditions, while CX3CR1 is predominantly expressed in microglia, which are a type of mononuclear macrophage in the central nervous system (26,27). Under physiological conditions, FKN can inhibit the activation of microglia and the release of inflammatory factors to protect brain tissue (28,29). Under pathological conditions, active microglia can release excitatory neurotoxins such as glutamic acid to stimulate in part the release of FKN from neurons (30), which was called sFKN.…”
Section: Discussionmentioning
confidence: 99%